How Does the Kingdom of Kutaringin Develop Educational Activities - Muslimah Muslimah; Khairil Anwar; Sabarudin Ahmad; Orisa Febriana (Ta'dib, 2023)
The Kingdom of Kutaringin is a kingdom which is the center of the spread of Islam in Central Kalimantan, especially in the western region. This research investigation was carried out to review the role of the Kutaringin kingdom and figures who played a role in educational activities through civilization that has been built over the years so that the benefits can be felt until now. This study uses empirical research with historical and religious approaches as a means of public education. Data collected using documentation, observation and interview techniques were validated using source and triangulation techniques. There were analyzed through the stages of heruistic, criticism, interpretation and historiography. The results showed that the development of educational activities in the Kutaringin kingdom began with the presence of mosques, palaces and artifacts as a means of public education. Apart from that, the Kyai Gede Mosque also had an important role in developing Islam in society, especially introducing the ahlusunnah wal congregation school. There is also the role of the palace, namely the Yellow palace, the Mangkubumi palace, and the Al-Nursari palace which have involvement in strengthening kinship unity and increasing friendship. In addition, it is a place to establish a sense of togetherness in the principle of a peaceful life and a form of pride. The Kutaringin Kingdom left artifacts in the process of developing Islam as proof that it still has its own style in its existence giving the role of educational activities. Islamization also carries out Islamic education activities that teach writing and memorization, skills in healing and teaching about morals. Then, the figure who plays a role in the development of educational activities is a king who has been passed down from generation to generation.